Topical Cannabinoids for Treating Chemotherapy-Induced Neuropathy: A Case Series - Stacy D’Andre MD (SAGE Publishing, 2021)
Background Chemotherapy-induced peripheral neuropathy is a common and often severe side effect from many chemotherapeutic agents, with limited treatment options. There is no literature on the use of topical cannabinoids for chemotherapy-induced neuropathy. Case Presentations The current manuscript presents a case series of patients presenting in oncology clinics at Sutter Health, CA and Mayo Clinic, Rochester, MN from April 2019 to December 2020 with chemotherapy-induced peripheral neuropathy who used topical creams containing the cannabinoids delta-nine-tetrahydrocannabinol (THC) and/or cannabidiol (CBD). Conclusions This case series suggests that topical cannabinoids may be helpful for patients with chemotherapy-induced peripheral neuropathy. This paper also discusses the potential mechanisms of action by which topical cannabinoids might alleviate established CIPN symptoms. A randomized placebo-controlled trial using a standardized product is planned to study the actual efficacy of such treatment.